2022
DOI: 10.3389/fpsyg.2022.884606
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Social Support Influence Junior College Students’ Occupational Identity in Pre-school Education?

Abstract: ObjectiveThis study aimed to investigate the multiple mediating effects of achievement motivation and subjective wellbeing between social support and individual occupational identity.MethodsQuestionnaire method was used in this study. 565 junior college students majoring in pre-school education were tested by social support scale, achievement motivation scale, subjective wellbeing scale, and occupational identity scale.Results(1) There isn’t significant relationship between perceptions of social support and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…In this study, we found that achievement motivation had an independent mediating role between receiving social support and professional identity, which was consistent with the results of Huang [49] et al Based on Herzberg's Two-Factor Theory, receiving social support could promote some external factors relating to health professional students' professional satisfaction, such as occupational environment and interpersonal relationships, and thereby enhance achievement motivation [83]. health professional students' achievement motivation refers to their intrinsic drive to achieve academic and professional achievement.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we found that achievement motivation had an independent mediating role between receiving social support and professional identity, which was consistent with the results of Huang [49] et al Based on Herzberg's Two-Factor Theory, receiving social support could promote some external factors relating to health professional students' professional satisfaction, such as occupational environment and interpersonal relationships, and thereby enhance achievement motivation [83]. health professional students' achievement motivation refers to their intrinsic drive to achieve academic and professional achievement.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, giving social support can also promote individuals' estimation on the possibility of success and improve their motivation to pursue success by supporting them both socially and psychologically. A study on college students showed that achievement motivation can increase the level of professional identity of college students majoring in preschool education [49], which was consistent with the results of Ge [50] on general practitioners. Above all, we hypothesized that achievement motivation might have mediating effects between receiving and giving social support and professional identity (Referred as H2 in this article).…”
Section: The Mediating Effect Of Achievement Motivationsupporting
confidence: 76%
See 2 more Smart Citations
“…Second, since achievement motivation positively predicts the research creativity of doctoral students, supervisors and departments can take steps to enhance it. Previous studies have shown that a supportive academic atmosphere and learning environment are key elements in enhancing students' achievement motivation (Baeten et al, 2013;Huang et al, 2022). Therefore, it is important to create a supportive and tolerant academic environment in which doctoral students are encouraged to address research challenges.…”
Section: Practice Implicationsmentioning
confidence: 99%